2004
DOI: 10.1046/j.0022-202x.2003.22110.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Hair Follicle Size and Distribution in Different Body Sites

Abstract: For the evaluation and quantification of follicular penetration processes, the knowledge of variations of hair follicle parameters in different body sites is basic. Characteristics of follicle sizes and potential follicular reservoir were determined in cyanoacrylate skin surface biopsies, taken from seven different skin areas (lateral forehead, back, thorax, upper arm, forearm, thigh, and calf region). The highest hair follicle density and percentage of follicular orifices on the skin surface and infundibular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
267
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(296 citation statements)
references
References 19 publications
(21 reference statements)
16
267
1
3
Order By: Relevance
“…in contrast, in adults, the corresponding values on the occipital scalp have been measured to be only 239 and 292-455 per cm 2 [49][50][51]. The hair follicle density in adults is significantly lower (14-90 follicles.cm -2 ) at other body sites, but comparable values are not available for new-borns [50].…”
Section: The Development Of Skin Barrier Functionmentioning
confidence: 93%
See 1 more Smart Citation
“…in contrast, in adults, the corresponding values on the occipital scalp have been measured to be only 239 and 292-455 per cm 2 [49][50][51]. The hair follicle density in adults is significantly lower (14-90 follicles.cm -2 ) at other body sites, but comparable values are not available for new-borns [50].…”
Section: The Development Of Skin Barrier Functionmentioning
confidence: 93%
“…The hair follicle density in adults is significantly lower (14-90 follicles.cm -2 ) at other body sites, but comparable values are not available for new-borns [50]. More recently, video-dermatoscopy was used to characterize five areas of the scalp in 45 neonates, and identified that two clinical patterns, namely "good hair density" (GHD) and "poor hair density" (PHD) can be present at birth.…”
Section: The Development Of Skin Barrier Functionmentioning
confidence: 99%
“…This includes the fine, peachwhite hypopigmented, nonmedullated vellus hairs that ordinarily cover most of the body and constitute facial down. The facial skin presents a remarkably elevated concentration of follicles in the postcranial anatomy, especially across the nose [25,26,27]. In living subjects, only 2-3mm of the vellus hair is exposed on the skin surface [28].…”
Section: External Skin Structurementioning
confidence: 99%
“…One can obtain some support for this idea by comparing the distribution of CMM with the distribution of androgenic body hair over male and female body sites. Males have more hair that is androgenic on their face, neck, and torso while females have more hair that is androgenic on their lower limbs [21] coincident with the body sites CMM is found most frequently. [22] Because outdoor workers have a lower CMM incidence than indoor workers, [17] yet they get three to ten times the annual UV radiation (UVR; 290 nm -400 nm) dose that indoor workers get, [23] we know the cumulative dose of UVR is not involved in CMM.…”
Section: Introductionmentioning
confidence: 99%